2021 11th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applicat 2021
DOI: 10.1109/idaacs53288.2021.9660960
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Intelligent Robotic System for Plasma Processing of Industrial Products with Complex Shape

Abstract: The paper presents new results of automated path planning for an industrial robot manipulator performing microplasma spraying of coatings on substrates with complex surface shapes. Path planning and automatic generation of the manipulator motion program are performed using data of a preliminary 3D surface scanning by a laser triangulation distance sensor installed on the same robot arm. The automatic manipulator working tool path planning algorithm is based on the choice of the starting segment of the working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…While the functionality and biocompatibility of prostheses are still being improved with more traditional approaches such as surface modification [9][10][11], new technologies are being developed. These primarily include the use of AM to print patient-specific implants [7,12,13], the thermal plasma spray of multilayer biocompatible coatings [14,15], and the automation (robotics) of related technological processes [15][16][17][18].…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
See 3 more Smart Citations
“…While the functionality and biocompatibility of prostheses are still being improved with more traditional approaches such as surface modification [9][10][11], new technologies are being developed. These primarily include the use of AM to print patient-specific implants [7,12,13], the thermal plasma spray of multilayer biocompatible coatings [14,15], and the automation (robotics) of related technological processes [15][16][17][18].…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
“…Last but not least, AM demonstrates the ability to integrate with other advanced technologies such as ultrafast lasers [29] or coating technologies such as robotic microplasma spraying (MPS) [18], microarc oxidation (MAO) [25], and wire and arc plasma spraying [30], which opens up opportunities for a new generation of micro-manufacturing techniques for difficult-to-machine materials.…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kalita et al [12] reported the production and successful clinical trials of titanium implants with 3D bioactive plasma titanium coating in dogs. Kussaiyn-Murat et al [13] used an industrial robotic arm for microplasma layer-by-layer spraying of tantalum coatings on a titanium implant, ensuring the movement of the robot along a 3D model obtained by scanning the implant surface. There is still a steady interest in increasing the biocompatible properties of the surface of metal implants using coatings from materials based on calcium phosphate [14].…”
Section: Introductionmentioning
confidence: 99%